(untitled) (Revista Contexto & Saúde, 2025)
This is a cross-sectional study analyzing the medical prescriptions of elderly people being treated for hypertension or diabetes mellitus at a Primary Health Care Unit in the Federal District, with the aim of identifying polypharmacy, potentially inappropriate medications (PIM), potential drug interactions (PDI) and the frequency of medications in continuous use according to clinical indication. Among the 1,245 prescriptions analyzed, 73.7% had polypharmacy, 95.6% contained at least one antihypertensive and 63.1% had an antidiabetic. In 301 (24.2%), a PIM or PDI was identified. The most frequent PIM was insulin, present in 13.7% (n=301; 56.5%). The most frequent PDI was between angiotensin II receptor blockers and potassium-sparing diuretics, present in 4.5% (n=301; 18.6%) of prescriptions. Polypharmacy was prevalent, especially among female patients. The most frequent PIM has an increased risk of causing hypoglycemia in the elderly, while the most identified PDI increases the risk of hyperkalemia and kidney damage. It is necessary to publicize and promote adherence to the clinical protocols and lines of care for controlling chronic diseases and to the lists of PIMs and PDIs for the elderly.